The Impact of Total Quality Management in the Training of Teachers at Maktab Perguruan Perempuan Melayu Melaka - Ahmad, Mariam (1997)
The current demand for quality education has immense implication on teacher training programs in Malaysia. The teacher training programs cover a wide perspective encompassing the academic, professional and personal development of teacher. Therefore, in the pursuit of training excellent teachers, Total Quality Management (TQM) was introduced in MPPM in 1992. The change towards TQM was aimed at achieving the concept of quality teachers, excellent staff and world class education. The objective of training quality teachers would mean being able to produce excellent teachers by means of efficient administration, having highly competent staff and smooth operation. Th